What are character strengths good for? A daily diary study on character strengths enactment. Issue 5 (3rd September 2022) - Gander, Fabian; Wagner, Lisa; Amann, Lukas; Ruch, Willibald
ABSTRACT: While character strengths are expected to contribute to the 'good life, ' they also may serve specific purposes (e.g., the strength of curiosity should support the acquisition and use of knowledge). This study explored the potential functions of character strengths from a within-person perspective. We used a literature review and qualitative and quantitative surveys to determine potential functions. This resulted in 17 distinguishable functions (e.g., 'feeling free and independent'). We used a diary study that included N = 196 participants (84.4% women, mean age: 25.68 years) who reported their daily character strength enactments and their experiences of the functions for 14 consecutive days. Our results suggested that the enactment of character strengths was positively related to several functions. However, the character strengths also showed distinguishable patterns of relationships with the functions, which were largely in line with – but not limited to – the functions suggested in the VIA classification.